Local Culture-Based Music Game Model for Early Childhood Education - Suwono (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2022)
Many music experts and educators have researched to see the positive effects of several types of music. Music turns out to be able to affect the intellectual development of children as well as make children wise to socialize. Many facts were revealed from this research. Among them, there is an exciting relationship between music and human intelligence. This study uses a qualitative methodology, with the research object being PIAUD IAIMNU Metro Lampung students. The results of this study indicate that playing music can increase a child's intelligence level because it includes sensitivity to mastery of rhythm, tone patterns, rhythms, tempos, instruments, and musical expressions to be able to sing a song or play it. Learning or playing in early childhood has several advantages, including being able to hone memory because children will recognize and try to memorize the tones of the music.